(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Antenatal care (ANC) is essential to prevent maternal and neonatal complications, yet Pakistan continues to report a high maternal mortality rate (276 per 100,000 live births) and neonatal mortality rate (55 per 1,000). Assessing women’s knowledge of ANC is critical to improving health outcomes. Objective: To assess the knowledge of pregnant women regarding antenatal care (ANC) and its relationship with demographic characteristics in tertiary care hospitals of Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted at a tertiary care hospital in Lahore from January to June 2024. A convenient sampling technique was used to recruit 100 pregnant women and data collected from them using an adopted questionnaire. Results: Over half of the participants (51%) had poor knowledge of ANC, 43% demonstrated average knowledge, and only 6% showed good understanding. Notably, 67% could not define ANC, 65% were unaware of the appropriate timing for the first checkup, and 59% did not recognize the need for at least four ANC visits. Similarly, 67% were unaware of the harms of smoking, 65% of alcohol risks, and 67% did not know the correct response in case of pregnancy complications. Education and occupation were significant determinants of ANC awareness. Conclusion: The findings reveal substantial knowledge gaps among pregnant women regarding ANC, highlighting the urgent need for targeted educational interventions, community-based awareness campaigns, and improved counseling by healthcare providers to reduce preventable maternal and neonatal deaths in Pakistan.